UCP2 and ANT differently modulate proton-leak in brain mitochondria of long-term hyperglycemic and recurrent hypoglycemic rats - Cardoso, Susana (2013)
A growing body of evidence suggests that mitochondrial proton-leak functions as a regulator of reactive oxygen species production and its modulation may limit oxidative injury to tissues. The main purpose of this work was to characterize the proton-leak of brain cortical mitochondria from long-term hyperglycemic and insulininduced recurrent hypoglycemic rats through the modulation of the uncoupling protein 2 (UCP2) and adenine nucleotide translocator (ANT). Streptozotocin-induced diabetic rats were treated subcutaneously with twice-daily insulin injections during 2 weeks to induce the hypoglycemic episodes. No differences in the basal proton-leak, UCP2 and ANT protein levels were observed between the experimental groups. Mitochondria from recurrent hypoglycemic rats presented a decrease in proton-leak in the presence of GDP, a specific UCP2 inhibitor, while an increase in proton-leak was observed in the presence of linoleic acid, a proton-leak activator, this effect being reverted by the simultaneous addition of GDP. Mitochondria from longterm hyperglycemic rats showed an enhanced susceptibility to ANT modulation as demonstrated by the complete inhibition of basal and linoleic acid-induced proton-leak caused by the ANT specific inhibitor carboxyatractyloside. Our results show that recurrent-hypoglycemia renders mitochondria more susceptible to UCPs modulation while the protonleak of long-term hyperglycemic rats is mainly modulated by ANT, which suggest that brain cortical mitochondria have distinct adaptation mechanisms in face of different metabolic insults.